Screening of antidiabetic and antioxidant potential along with phytochemicals of Annona genus: a review - Shadman Sakib Chowdhury; Abu Montakim Tareq; Syed Mohammed Tareq; Saifuddin Farhad; Mohammed Abu Sayeed (SpringerOpen, 2021)
Abstract Background Annona species can be found in the subtropical and tropical parts of the world. Because of their medicinal capabilities and highly exotic edible fruits, they are one of the most important members of the Annonaceae family. Isoquinolines, pyrimidine-β-carboline alkaloids, lectins, acetogenins, and volatile oils are among the active metabolites found in this genus, all of which have been shown to have anti-diabetic and antioxidant activities. Main body The fundamental objective of this review was to summarize the antidiabetic and antioxidant activity based on reported secondary data from different plants of the genus Annona. These species include Annona cherimola, Annona squamosa, Annona macroprophyllata, Annona muricate, Annona reticulata, Annona carcans, Annona coriacea, Annona cornifolia, and Annona senegalensis. The Annona species investigated had significant antihyperglycemic and antioxidant properties. Conclusion The available evidence, both in vitro and in vivo, confirms the ability of Annona species to treat diabetes in addition to producing oxidative damage.